Pengaruh Konvergensi Standar Akuntansi Keuangan (SAK) Berbasis International Financial Reporting Standard (IFRS) Terhadap Kualitas Audit - ARFAN, Adi Prawira ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Quality of an audit process is very important to ensure that financial statement can be used as a basis for decision making and can be trusted by the public or other third parties. Many factors can affect audit quality both positively and negatively. The issue of earnings management has always been a concern for the reliability of published accounting reports. Accounting can not be separated from the effects of globalization. a series of movements that began in 1973 has made International Accounting Standards Committee (IASC). IASC which in 2001 changed to the International Accounting Standard Board (IASB) set international standard, IFRS, aims to develop a high-quality accounting standards, can be understood, and applied globally throughout the world. This study wanted to examine how the effect of IFRS-based SAK, which was implemented in Indonesia began in 2011, to audit quality. To test this, the study saw the GAAP-based test whether IFRS have a moderation role that strengthens the quality of audit and accrual earnings management. Audit quality in this study is measured by the size of KAP, KAP tenure, and industry specialization KAP. The sample used in this study is a company listed on the Indonesia Stock Exchange with a total sample of 930 firm-year observation period of years by 2007-2011. The test results of this study indicate that the size of the KAP, KAP tenure, and industry specialization KAP has a negative relationship with earnings management. Based on the test results of all audit quality measures used in this study, has not found sufficient evidence that IFRS-based SAK has a moderate role that strengthen audit quality on accrual earnings management. From the regression results, showing moderate of GAAP-IFRS to KAP tenure and industry specialization KAP and showed no moderation relationship to the size of the KAP. This suggests that the study did not find sufficient evidence that GAAP-based IFRS impact on audit quality. Sensitivity test results also showed results in line with the test results of the study.